Proceedings the 2nd conference on food science & technology : (Cantho University, 2013)
Contents: Reduction of Coliform bacteria in pennywort by dipping in ozone water and organic acid solutions, Influence of leptin genotypes on fat and protein content in crossbred Holstein Friesian cow's milk, Technological parameters and correlations among pork quality traits in Longissimus dorsi muscle,...